Effective treatment of oily sludge for biogas and methane gas production at mesophilic using anaerobic batch reactor (AnBR) - Kumar, V. (Elsevier Ltd, 2022)
The oily sludge is one of the toxic organic sludge generated from petroleum oil refineries plants and categorized as priority pollutants. Anaerobic batch treatment using bacteria species is a key strategy for treating toxic pollutants. The present study aims to produce biogas and methane gas at mesophilic conditions by using potential bacteria existing in oily sludge. The oily sludge was found rich in microorganisms adapted to extreme toxic organic waste and capable of adjusting to severe environmental conditions. The potential microorganism was isolated by enrichment technique to analyze the potential of the isolated strains to assimilate under lab scale. Anaerobic batch treatment at mesophilic temperature of Â±35 Â°C, pH (6â8), 60 rpm mixing for 21 days with sample feed of 1L, 1.5L and 2L of oily sludge to produce biogas and methane gas by water displacement method. The results from anaerobic batch treatment shows that total biogas yield obtained, including methane yield of 25369 mL and 3900 mL, respectively at optimum feed volume of 2L. Overall, the study's findings revealed that oily sludge has the potential bacteria to produce the amount of biogas and methane gas. The large amount of oily sludge can be recycled, which will reduce environmental contamination. The investigations from the current study will help with the feasibility of oily sludge treatment in the future. Â© 2022